Strategy for the renaissance of Bulgarian industry: policy planning vs implementing measures - Kopeva, Diana; Sterev, Nikolay; Blagoev, Dimitar (Economics of the 21st Century, 2018)
A wide range of strategic documents outlines the “road map” of development of the existing industry to “Industry 4.0” in Bulgaria. Despite efforts at European and national level, the implementation of the “road map” for the reindustrialization of the economy meets a basic problem of how to plan without evolution to achieve a revolution in the industry. As a result of the realization of this problem, there is an absence of a clear European or national plan to implement the “revival of industry” with the available economic, social, and political contexts, but at the same time, a realization of short-term plans is observed, aimed primarily at using investment measures to change the industry from the “inside”. This report emphasizes the main challenges facing a strategic plan for the reindustrialization of the Bulgarian economy as well as structurally addresses the following questions: 1. What are the Bulgarian strategic and operational documents related to the implementation of a common European plan for revival of the industry to “Industry 4.0”? 2. What short-term measures should be implemented as the first steps in Bulgaria in this direction? Summary and conclusions end the article
Ekonomia XXI Wieku = Economics of the 21st Century, 2018, Nr 2 (18), s. 7-16
Keywords: industrial renaissance; reindustrialization; Bulgarian economy; strategic planning; policy measures; renesans przemysłowy; reindustrializacja; gospodarka bułgarska; planowanie strategiczne; środki polityczne